Rancang Bangun E-Enrollment Berbasis Web Menggunakan Customer Relationship Management (CRM) Pada Sekolah Dasar Islam Terpadu - Syamsul Bahri; Sopiyan Dalis (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
Utilization of Internet technology can play an important role in the effort to perform any transaction. Especially in the process of Penerimaan Peserta Didik Baru (PPDB) which has been mostly done by manual system, or when already utilizing the latest information technology but did not happen the process of information feedback, eg the notification via email about the information already received input data from the form and how how to pay online. Today's technology is Internet technology that has the privilege to know information in other parts of the world without being impeded by the distance, time and place. With these considerations, it is necessary to solve all obstacles, especially in the case of the implementation of new students' admissions at Sekolah Dasar Islam Terpadu (SDIT). This research was conducted to maximize the utilization of web-based information technology by using Customer Relationship Management (CRM) method so that the new student e-enrollment system at SDIT Nahwa Nur can be more effective and efficient.Key Word: web, waterfall, Customer Relationship Management (CRM)